Author Topic: Quiz 4 (TUT0601)  (Read 490 times)

etheliachoi

  • Newbie
  • *
  • Posts: 1
  • Karma: 0
    • View Profile
Quiz 4 (TUT0601)
« on: October 18, 2019, 10:47:11 PM »
Find the general solution of this equation:

y''+y'-6y = 12e3t+12e-2t


Find the homogenous solution:

y''+y'-6y=0

r2+r-6r=0

(r+3)(r-2)=0

r1 = -3, r2 = 2

y1(t)= e-3t, y2(t)= e2t

Then,
y(t) =c1e-3t + c2e2t

Now, consider
y''+y'-6y = 12e3t

Want to find:
Y(t) = Ae3t

Y'(t) = 3Ae3t, Y''(t) = 9Ae3t

Then,
9Ae3t + 3Ae3t - 6Ae3t = 12e3t

Thus, solving the equation, we get that:
A = 2 and Y(t) = 2e3t

Now, consider
y''+y'-6y = 12e-2t

Want to find:
Y(t) = Be-2t

Repeat for the process for Y(t) and solve for B. Hence, we get that
B = -3 and Y(t) = -3e-2t

Lastly,
y = c1e-3t + c2e2t + 2e3t - 3e-2t